Reputation: 67
syms Gr Ra Ri A B Gr1 Gr2 c d
Gr = 2*c*(Ra^2 - Ri^2) - d*(Ra^4 - Ri^4)/2;
Gr1 = subs(Gr, [c*(Ra^2 - Ri^2), -d*(Ra^4 - Ri^4)/2], [A, B])
Gr2 = subs(Gr, [c*(Ra^2 - Ri^2), d*(Ra^4 - Ri^4)/2], [A, B])
returns
Gr1 =
2*A + B
Gr2 =
2*A - (d*(Ra^4 - Ri^4))/2
Is there a way to convince MATLAB to return Gr2 = 2*A - B
in the second case without workarounds? I have a much more complex expression to substitute, but I can't work with this subs()-behaviour. Thanks.
Upvotes: 5
Views: 564
Reputation: 67
The described behaviour was classified by the Matlab development team as unexpected and will hopefully be fixed in future releases:
Upvotes: 0
Reputation: 1345
I think the problem is in the multiplication/division operations in the second argument of subs
since the problem vanishes once I rearrange the code as follows:
syms Gr Ra Ri A B Gr1 Gr2 c d
Gr = 2*c*(Ra^2 - Ri^2) - d*(Ra^4 - Ri^4)/2;
Gr1 = subs(Gr, [(Ra^2 - Ri^2),(Ra^4 - Ri^4)], [A/c,-2*B/d])
Gr2 = subs(Gr, [(Ra^2 - Ri^2),(Ra^4 - Ri^4)], [A/c,2*B/d])
and the output is:
Gr1 =
2*A + B
Gr2 =
2*A - B
Upvotes: 1